International Medieval Institute, University of Leeds, International Medieval Bibliography, 6 (1967-1998), Thurnout, Brepols Publishers, 2000, CD-ROM - Corrao, Pietro (Reti Medievali Rivista, 2001)
Recensione a: International Medieval Institute, University of Leeds, International Medieval Bibliography, 6 (1967-1998), Thurnout, Brepols Publishers, 2000, CD-ROM